Global Warming: Its Causes and solutions - Aneet, (Gyan Management Journal, 2014)
Global warming is primarily a problem of too much carbon dioxide (CO2) in the atmosphere-which acts as a blanket, trapping heat and warming the planet. As we burn fossil fuels like coal, oil and natural gas for energy or cut down and burn forests to create pastures and plantations, carbon accumulates and overloads our atmosphere. Certain waste management and agricultural practices aggravate the problem by releasing other potent global warming gases, such as methane and nitrous oxide. See the pie chart for a breakdown of heat-trapping global warming emissions by economic sector.It took more than 20 years to broadly accept that mankind is causing global warming with the emission of greenhouse gases. The drastic increase in the emission of CO2 ( carbon dioxide) within the last 30 years caused by burning fossil fuels has been identified as the major reason for the change of temperature in the atmosphere. More than 80% of the worldwide energy demand is currently supplied by the fossil fuels coal, oil or gas. It will be impossible to find alternative sources, which could replace fossil fuels in the short or medium term. The energy demand is simply too high.
Keywords: Global warming; CO2; planet; breakdown; greenhouse